2012
DOI: 10.1074/jbc.m112.369496
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of α-Catulin with Dystrobrevin Contributes to Integrity of Dystrophin Complex in Muscle

Abstract: Background:The dystrophin complex stabilizes the cell membrane by linking the cytoskeletal network to the extracellular matrix. Results: ␣-Catulin interacts directly with dystrobrevin, a component of the dystrophin complex, in muscle. Conclusion:The interaction of ␣-catulin with dystrobrevin contributes to the integrity of the dystrophin complex in muscle. Significance: A molecular interaction potentially important for muscle pathogenesis is identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…S3A). This is in agreement with previous observations for α-catulin (Oh et al, 2012). Similar results were obtained after electroporation of GFP-fusion constructs into muscle tissues.…”
Section: Identification Of α-Dystrobrevin-1-interacting Proteinssupporting
confidence: 82%
See 1 more Smart Citation
“…S3A). This is in agreement with previous observations for α-catulin (Oh et al, 2012). Similar results were obtained after electroporation of GFP-fusion constructs into muscle tissues.…”
Section: Identification Of α-Dystrobrevin-1-interacting Proteinssupporting
confidence: 82%
“…The one protein from this group that we considered further was the deubiquitinating enzyme Usp9x (Théard et al, 2010), which was highly enriched in α-dystrobrevin-1 complexes (79 peptides recovered) and virtually missing in the control purification. The remaining eight proteins comprised six components of the DGC [three syntrophin isoforms, two dystrobrevin isoforms and utrophin (Sunada and Campbell, 1995)]; α-catulin, which we and others have previously shown to bind to α-dystrobrevin (Lyssand et al, 2010;Oh et al, 2012); and liprin-α1, a scaffold protein previously shown to interact with α-catulin (Lyssand et al, 2010;Spangler and Hoogenraad, 2007;Spangler et al, 2011) (Fig. 3B).…”
Section: Identification Of α-Dystrobrevin-1-interacting Proteinsmentioning
confidence: 99%
“…Exaggerated head bending has previously been observed by numerous independent research groups in mutants with loss-of-function mutations to dys-1 , the C. elegans ortholog of human Dystrophin, and to components of the Dystrophin associated protein complex (DAPC) (Fig. S1A) (Oh et al . 2012; Kim et al .…”
Section: Resultsmentioning
confidence: 83%
“…Dystrobrevin and syntrophin, which are components of the Dystrophin-associated protein complex, have C. elegans orthologs which interact with with C. elegans DYS-1 (Grisoni et al . 2003; Oh et al . 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation